Identifikasi komponen harmonik di Selat Lombok berdasarkan data arus time series - Rizal Fadlan Abida; Widodo Setiyo Pranowo; Yogo Pratomo; Engki Andri Kisnarti (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2015)
Abstract. Lombok Strait is one part of Indonesia Through Flow (ITF), important for national and international maritime economic. The strait is passed by ITF, i.e., a displacement water from the Pacific Ocean into the Indian Ocean caused by a difference in the sea water level. ITF flows across the Makassar Strait to south direction and passes through the smaller straits along Bali to Flores. ITF pattern is influenced by its local area condition which creates unique characteristics in each place. ITF passes through the Lombok Strait in part directly related to the Indian Ocean, as well as a very diverse state bathymetry of shallow ocean to ocean trenches. Various oceanographic phenomena affect ITF in the Lombok Strait: tides and waves are formed due to the interaction between the ocean currents from the Indian Ocean to the Lombok Strait, met with ITF flowing from the Lombok Strait into the Indian Ocean. As tides, currents are influenced by the tides that have harmonic components, but there are differences in the frequency and phase are formed. Harmonic component is one of indicators in determining the characteristics of a body of water. The purpose of this study is to obtain the derived harmonic components by analysing currents data in the Lombok Strait acquired from The International Nusantara Stratification and Transport (INSTANT) Expedition Mooring Deployment 1 conducted in 2004 to 2005. Based on the analysis it is known that the characteristic harmonic currents in the Lombok Strait is influenced by significant harmonic components such as Solar Semi Annual (SSA) and Solar Annual (SA)constituents be used, as the result of harmonic analyses of tidal data at ports all over the world reveal that they are dominated by the seasonal variations of sun.Keywords : ITF; Sea Current; Harmonic Component; INSTANT ExpeditionAbstrak. Selat Lombok merupakan salah satu alur lintas kepulauan Indonesia (ALKI) yang penting bagi perekonomian maritim nasional dan internasional, sekaligus sebagai alur dari arus lintas Indonesia (Arlindo). Arlindo merupakan peristiwa perpindahan masa air dari Samudera Pasifik menuju Samudera Hindia, yang disebabkan oleh perbedaan ketinggian air laut. Jalur Arlindo melintasi Selat Makasar menuju selatan, kemudian terbagi melewati selat-selat yang lebih kecil diperairan Bali hingga Nusa Tenggara Timur. Pola Arlindo dipengaruhi keadaan perairan setempat yang dilewatinya, sehingga Arlindo memiliki karakteristik yang unik pada masing-masing tempat. Pada Selat Lombok yang berhubungan langsung dengan Samudera Hindia, fenomena oseanografi mempengaruhi ARLINDO di Selat Lombok diantaranya adalah pasang surut dan internal wave yang terbentuk karena interaksi antara arus laut dalam yang berasal dari Samudera Hindia menuju Selat Lombok. Arus pasut memiliki komponen harmonik seperti gaya pembangkitnya, namun terdapat perbedaan pada frekuensi dan fasa yang terbentuk. Komponen harmonik pasut dan arus pasut merupakan salah satu indikator dalam penentuan karakteristik suatu perairan. Tujuan dari penelitian ini adalah untuk memperoleh besaran komponen harmonik yang diturunkan dari arus di Selat Lombok dari Ekspedisi INSTANT Mooring Deployment 1 yang dilaksanakan pada tahun 2004 hingga 2005. Berdasarkan analisis harmonik diketahui bahwa karakteristik arus di Selat Lombok dipengaruhi oleh komponen harmonik signifikan seperti Solar Semi Annual dan Solar Annual yang merupakan komponen yang dipengaruhi oleh pergerakan matahari secara paruh tahun maupun tahunan.Kata kunci : Arlindo; Arus Laut; Komponen Harmonik; Ekspedisi INSTANT